NUTRITIONAL VALUES OF MOLOKHIA STICKS AND ITS USE AS A FEED ALTERNATIVE FOR AWASSI LAMBS (Journal of Hama University, 2023)
The study was conducted on 12 lambs of Awassi sheep, with an average weight of 26.5 kg, with an average age of 3 months, within a closed breeding system pen divided into two sections with fixed walls. The experiment lasted 110 days.The lambs were randomly distributed into two equal groups. The lambs were fed a standardized concentrated diet for 110 days with a protein content of 17.11%. The difference between the two experiment groups was only in the full feed, where the first group was given hay as a full feed, while the second group was given dried mallow sticks with a ratio of 83 % as a filler feed, in order to know the nutritional value of the mallow sticks and the possibility of using it as a cheap (economically feasible) filler feed alternative for Awassi lambs.The results of the analysis of samples of hay and dried mallow sticks showed that 83% of dried mallow sticks were superior in crude protein content of 7.6% and metabolic energy 2200 kWh/kg compared to straw in which the percentage of crude protein was 2.3% and the metabolic energy was 754 kk. /kg.The results also showed a significant increase at the level of P≤0.05 in the average total weight gain of the lambs of the second group (which ate dried mallow sticks) 24.25 ±0.80 kg compared with the total weight gain of the lambs of the first group 21.00 ±0.48 kg, and the results also showed a significant increase at the level of P ≤0.05 in the average daily weight gain of lambs of the second group 226.62 ±7.46 g compared with the average daily weight gain of lambs of the first group 196.26 ±4.52 gThe results indicated that the nutritional value of the mallow sticks outweighed the nutritional value of the straw and that it was possible to use the dried mallow sticks as a filler feed with less material cost (economic feasibility) and educational results (weight gain).
Keywords: Molokhia sticks - Full feed - Nutritional value - feed alternative - Awassi lambs.